Chances of Coping with Having Disabled Children for Families in Rumania (European Journal of Mental Health, 2009)
Most studies deal with the way of how the hardships and stress aroused by the deficiency affect the family, the family relations and roles. However, some families having children with disabilities can face their situation due to their personality resources, their environment or with the help of social services. The article presents the results of a research on the coping strategies of parents with disabled children. The sample consists of 400 Rumanian families who brought up a disabled person aged 0 to 23. The primary intention of the research was to provide as much information as possible about the families having disabled children, based on which it can be explored how they fight against the situation of life changed by the deficiency. The other aim of the research was to explore the situation of the families living with deficiency through examining the risk and resiliency factors, and to investigate how those families can find those supportive possibilities in their immediate circumstances, in the supplies provided by the supplysystem and in their own personalities which make it possible for them to stay balanced in spite of the problems. This paper is looking for protective factors and solutions, which are helpful for parents in finding successful coping strategies. It also examines risk factors, which usually lead to a lack of balance in the family life and makes coping difficult.